2021
DOI: 10.1108/jd-08-2021-0158
|View full text |Cite
|
Sign up to set email alerts
|

Serious information in hedonic social applications: affordances, self-determination and health information adoption in TikTok

Abstract: PurposeHedonic social applications have been increasingly popular among health information consumers. However, it remains unclear what motivates consumers to adopt health information in hedonic applications when they have alternative choices of more formal health information sources. Building on the self-determination theory and the affordances lens, this study aims to investigate how different affordances on hedonic social applications affect consumers' basic psychological needs and further influence their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Recently, some researchers have suggested that video-based social media such as TikTok are playing increasingly important roles in providing general health information sought or encountered by consumers [40,41]; therefore, health experts and traditional institutions should harness and leverage social media platforms and apps to better disseminate health information and medical knowledge to the public [41,42]. In general, the findings of this study indicate that health professionals and reputable organizations are actively engaged in communicating health information on TikTok.…”
Section: Sources Of Copd-related Videos On Tiktokmentioning
confidence: 66%
“…Recently, some researchers have suggested that video-based social media such as TikTok are playing increasingly important roles in providing general health information sought or encountered by consumers [40,41]; therefore, health experts and traditional institutions should harness and leverage social media platforms and apps to better disseminate health information and medical knowledge to the public [41,42]. In general, the findings of this study indicate that health professionals and reputable organizations are actively engaged in communicating health information on TikTok.…”
Section: Sources Of Copd-related Videos On Tiktokmentioning
confidence: 66%
“…Szmuda et al [16] found that higher engagement was noted in stroke-related videos that were uploaded by an educational channel on YouTube. Recently, studies [21,22] have shown that the emerging short-video social apps can satisfy people's intrinsic motivations and elicit user engagement when disseminating health information. TikTok (DouYin in Chinese) is a short-video social app with a sizable userbase wherein individual users create and publicly post short videos on various subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Szmuda et al [ 16 ] found that higher engagement was noted in stroke-related videos that were uploaded by an educational channel on YouTube. Recently, studies [ 21 , 22 ] have shown that the emerging short-video social apps can satisfy people’s intrinsic motivations and elicit user engagement when disseminating health information.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al found that hedonic social applications such as TikTok are an important channel for users to access health information ( 11 ). TikTok affords rich information modalities and contains ample technology features such as commenting, chatting, liking, following, and live-streaming, which make the app easier for the users to use as a source of health information ( 11 ). TikTok learns quickly via artificial intelligence what users like ( 12 ), which results in more recommendations of hearing aids-related videos for users with hearing impairment.…”
Section: Introductionmentioning
confidence: 99%